Validação da versão brasileira do questionário World Health Organization Disability Assessment Schedule (WHODAS 2.0) para mulheres com incontinência urinária - Moura, Anna Caroline Ribeiro de (2022)
Introduction: Urinary incontinence (UI) is defined as the involuntary loss of any amount of urine. More prevalent in women, UI affects several aspects of quality of life, and can also affect women's functioning. Currently, the WHO strongly recommends health approaches and research based on the functioning model, as this approach the real difficulties faced by patients who have dysfunctions. The World Health Organization Disability Assessment Schedule (WHODAS 2.0) questionnaire was created with the purpose of evaluating the functioning of different groups of people with different health conditions. However, its psychometric properties when applied to women with UI are not yet known. Objectives: To test the psychometric properties of the WHODAS 2.0 instrument for women with urinary incontinence. Methods: Validation and reliability study of the WHODAS 2.0 questionnaire in the 36-item version. The research was carried out at the Maternidade Escola Assis Chateaubriand (MEAC) and at a private gynecology and pelvic physiotherapy clinic in Fortaleza/Ceará from March 2020 to June 2022. 18 years old, without cognitive disorders. Women with chronic pelvic pain of any etiology, severe pelvic organ prolapses and urinary incontinence of neurogenic origin were excluded. After obtaining the Free and Informed Consent Form, the instruments were applied through two interviews (the first being face-to-face and the second via telephone after 1 to 2 weeks). For the validation process of the World Health Organization Disability Assessment Schedule (WHODAS 2.0) instrument, the following auxiliary questionnaires were used: Mini Mental State Examination (MMSE), King's Health Questionnaire (KHQ) Severity Measures, Incontinence Severity Index (ISI), the International Incontinence Consultation Questionnaire (ICIQ-SF) and the Pelvic Floor Impact Questionnaire (PFIQ-7). The design of psychometric properties followed the taxonomy, definitions and guidelines of the Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN). Reliability was tested by Cronbach's alpha coefficient, test-retest reliability by the intraclass correlation coefficient (ICC), concurrent validity with the Spearman correlation, and construct validity with the hypothesis test by ANOVA. Results: 101 women with UI with a mean age of 50.71 years (SD±10.39) were included. WHODAS 2.0 showed good reliability in all domains and excellent reliability in the total score (Cronbach's alpha from 0.8). In test-retest reliability, ICC values were between moderate and good (ICC: 0.59 to 0.87 in the total WHODAS score). Regarding the analysis of concurrent validity, we observed a positive correlation of the WHODAS 2.0 domains with all the gold standard instruments, with a greater emphasis on moderate correlation for the participation domain (rho = 0.72 - p<0.001) and score total (rho = 0.73 – p<0.001) in relation to the PFIQ-7. Construct validity showed that WHODAS 2.0 was able to demonstrate greater impacts on the functioning of women with severe and very severe urinary incontinence. Conclusion: the WHODAS 2.0 instrument proved to be a reliable and valid questionnaire for the purpose of investigating the functioning and disability of women with urinary incontinence.